Implementasi Inquiry Learning melalui Aplikasi Google Classroom Mata Pelajaran Fiqih - Farida Isroani; Ulva Badi’ Rahmawati; Lukman Irfani (Multiverse: Open Multidisciplinary Journal, 2022)
This study aims to find out how the implementation of Inquiry Learning method learning through Google Classroom in Fiqh subjects, to find out the advantages and disadvantages of Inquiry Learning method learning through Google Classroom on Ijarah Fiqh subjects. The results showed that: the implementation of learning used when learning (online) used Google Classroom, namely the teacher referred to the government's recommendation, namely using one sheet of lesson plans. While the advantages of the Inquiry Learning learning method through the Google Classroom application include: (1) This inquiry learning can provide space for students to learn according to their style/desire, (2) Students become more independent during assignments, (3) increase creativity in learning. While the disadvantages of learning the Inquiry Learning method through the Google Classroom application include: (1) Internet signal/connection, (2) Limited Internet quota. (3) Teachers cannot supervise and supervise students during learning. The solution that will be solved by the researcher is by developing the inquiry learning provided, in the sense that students will be increasingly challenged by the problems given by the teacher. One of them is the use of audiovisuals or classrooms in Google Classroom. In addition, students can understand the material introduced by the teacher. Teachers can provide materials and assignments in the Google Classroom application, which also has the Meet feature available. So that it raises the idea of ??creativity and independence of students in learning according to their style.